What Booster Customer Advocacy?: The Mediating Role Of Customer Satisfaction In Fore Coffee Indonesia - Doflin Sen; Juniwati Juniwati; Bintoro Bagus Purmono; Nur Afifah; Harry Setiawan (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Intensifying competition in the coffee shop industry requires companies not only to focus on product innovation but also on creating experiences and café atmospheres that can stimulate customer advocacy behavior. Unlike previous studies that generally position product innovation, café atmosphere, and customer experience as direct predictors of loyalty, this study emphasizes customer advocacy as an advanced form of customer behavior and examines customer satisfaction as the main mediating factor. This study aims to analyze the effects of product innovation, café atmosphere, and customer experience on customer advocacy, with customer satisfaction as a mediating variable. A quantitative approach was employed, involving 220 Fore Coffee customers and analyzed using SEM AMOS version 29. The results indicate that all three independent variables significantly affect customer satisfaction. Café atmosphere and customer experience significantly influence customer advocacy, while product innovation does not. However, customer satisfaction significantly mediates all relationships. These findings highlight the central role of customer satisfaction as a psychological mechanism that bridges company stimuli and customer advocacy behavior. Product innovation, café atmosphere, and customer experience may not directly encourage customers to become brand advocates unless they successfully generate strong satisfaction.